An unusual case of steroid unresponsive Hashimoto’s encephalitis in Indian under-5 - Raut, Sumantra; Biswas, Antara; Datta, Kalpana (Indian Journal of Case Reports, 2022)
Hashimoto’s encephalopathy (HE) is a rare entity in children. Usually, it responds very well to steroids. We report a case of steroid-unresponsive HE in a 4-year-old male child presenting with acute encephalitis syndrome with raised intracranial pressure. Serum anti-thyroid peroxidase antibody was high. He was refractory to intravenous immune globulin and steroids. He underwent plasma exchange therapy which had a dramatic response with marked clinical improvement.